Legal Protection of Indonesian Workers on Japan on the Perspective of Human Rights and Pancasila Values - Franciscus Xaverius Wartoyo; Batubara, Aznina Lembayung; Harjono, Evy; Maghribi, Genta (Jurnal Smart Hukum (JSH), 2024)
In the 21st century, the phenomenon of labor migration is becoming increasingly significant globally. Japan has become one of the main destinations for Indonesian workers. However, legal protection for them in Japan is still a major concern. This study provides an in-depth insight into the challenges faced by Indonesian workers in Japan in obtaining adequate legal protection. Using a qualitative approach and text analysis, this research uncovers important aspects of legal protection for Indonesian workers in Japan. The findings highlight the need for an evaluation of the effectiveness of the legal protection provided, as well as an emphasis on its relation to the principles of human rights and the values of Pancasila. The legal protection provided should be in line with human rights principles, such as the rights to justice, equality and humanity. As a country based on Pancasila values, the practice of legal protection for Indonesian workers in Japan must also be consistent with Pancasila values, such as social justice, unity, and humanity. The recommendations from this research can serve as a foundation for improving the legal protection system for Indonesian workers in Japan, with the ultimate goal of improving their welfare and ensuring that their rights are properly recognized, respected and protected. As such, this research not only provides a better understanding of the challenges faced by Indonesian workers in Japan, but also offers directions that can be taken to improve their conditions in the future.